Through Centuries: From the Initial Conception towards Functional Obscurity (On the Emergence of a Peculiar Painting Detail on the Murals “Boddhisattva Manjuśrī” from the Bezeklik Monastery) - Kozlovskaia, Marina V. (Actual Problems of Theory and History of Art, 2017)
The Hermitage Museum has in its collection a large-size mural “Bodhisattva Mañjuśrī” dated to the 11th century, from the Bezeklik cave monastery, brought by S. F. Oldenburg from the First Turkestan expedition.This multifigure painting is a fairly traditional composition with Buddhas or bodhisattvas: Mañjuśrī is sitting on a lion surrounded by a retinue of several characters. At the bottom, under the image of the lion, there are two figures of boys, who could be interpreted as symbols of the souls of the righteous men reborn in the Pure Land. The group of artists who created the mural probably used the templates or sketches which possibly had been brought from the Mogao ku monastery (Dunhuang). It is widely known that the art of Hellenistic states of the East had a serious impact on the iconography of early Buddhism: numerous monuments show the attempts of borrowing both forms and techniques — from there volutionary contrappos to to the way of showing a body through clothing. Some of these forms and techniques over time entered iconographic canon or became traditional in depicting various personages in Buddhist art,but, with the time passing, the original ideas were lost, leaving behind just formal replicas — as in case of the perception and reproduction of contrapposto: a kneecap of a bent forward leg shown schematically as an oval.The oval gradually becomes not a depiction of a knee, but a sign of a knee and remains clearly emphasized evenon legs of the figures presented frontally. In the Hermitage “Mañjuśrī” composition these ovals even change their correct anatomical position — some of them are depicted in the middle of a tibia as on the legs of the boys. Later, the oval turns into the symbol of any major joint, and can be depicted not only on the projecting bends of the limbs, such as knees or elbows, but on a place of recess — between the foot lift and the beginning of the leg as itis seen on paws of the lion in the same mural.